2012
DOI: 10.5194/hess-16-4581-2012
|View full text |Cite
|
Sign up to set email alerts
|

Potential climate change impacts on the water balance of regional unconfined aquifer systems in south-western Australia

Abstract: Abstract. This study assesses climate change impacts on water balance components of the regional unconfined aquifer systems in south-western Australia, an area that has experienced a marked decline in rainfall since the mid 1970s and is expected to experience further decline due to global warming. Compared with the historical period of 1975 to 2007, reductions in the mean annual rainfall of between 15 and 18 percent are expected under a dry variant of the 2030 climate which will reduce recharge rates by betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…8). These results are comparable with previous studies under Mediterranean climate, which reported that the predicted reduction in groundwater recharge is two to four times the reduction in rain (Candela et al, 2009; Ali et al, 2012)…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…8). These results are comparable with previous studies under Mediterranean climate, which reported that the predicted reduction in groundwater recharge is two to four times the reduction in rain (Candela et al, 2009; Ali et al, 2012)…”
Section: Resultssupporting
confidence: 91%
“…8). hese results are comparable with previous studies under Mediterranean climate, which reported that the predicted reduction in groundwater recharge is two to four times the reduction in rain Ali et al, 2012) he model showed that the reduced rain scenario would lead to an increase in chloride concentration in the vadose zone ( Fig. 9).…”
Section: Impact Of Climate Change On Groundwater Rechargementioning
confidence: 99%
See 1 more Smart Citation
“…Lack of rainfall drives vegetation to consume soil water to survive, and this may explain a turning point in SM found between 2000 and 2003. Soil water availability would have affected the dynamics of not only non‐forest but also forest, and the predicted decline in rainfall (Ali et al, ) may further suppress vegetation growth.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1970s, this region has experienced a 10-20% decrease in average annual rainfall that resulted in a mean annual rainfall of 775 mm in the period 2004-2014 [40][41][42]. There is evidence that climate change has been impacting the hydrology of the unconfined aquifer since the 1970s [43][44][45], leading to less surface water availability [46,47]. Local-scale hydrologic changes associated with land-use change and groundwater abstraction may also impact water Climate change, via its impact on rainfall and groundwater recharge, is an important regional driver of wetland hydrology and ecological functions [38,39].…”
Section: Case Study Areamentioning
confidence: 99%